2012
DOI: 10.4049/jimmunol.1201256
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioside Inhibition of CD8+ T Cell Cytotoxicity: Interference with Lytic Granule Trafficking and Exocytosis

Abstract: Granule exocytosis-mediated cytotoxicity by CD8+ CTL plays a crucial role in adaptive immunity to tumors and to intracellular pathogens. This T cell effector function has been shown to be defective in various murine tumor models and in human cancer. However, factors and their mechanisms that cause inhibition of CD8+ T cell lytic function in tumor-bearing hosts remain to be fully defined. We postulate that gangliosides, highly expressed on tumor cell membranes, actively shed into the tumor microenvironment, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 43 publications
(38 reference statements)
0
21
0
Order By: Relevance
“…105,107 Furthermore, soluble gangliosides have been shown to disrupt nuclear factor kappa B (NF-B) function in immune cells 108,109 as well as lytic granule trafficking and exocytosis in CD8 C T cells. 110 Thus, gangliosides that are shed into the microenvironment can disrupt the normal functioning of T cells in numerous ways. Therapies targeting the tumor gangliosides GD2, GM3, and GD3 may potentially prevent gangliosides from inducing T-cell dysfunction.…”
Section: Molecular Mechanisms Of Immune Evasion By Tumorsmentioning
confidence: 99%
“…105,107 Furthermore, soluble gangliosides have been shown to disrupt nuclear factor kappa B (NF-B) function in immune cells 108,109 as well as lytic granule trafficking and exocytosis in CD8 C T cells. 110 Thus, gangliosides that are shed into the microenvironment can disrupt the normal functioning of T cells in numerous ways. Therapies targeting the tumor gangliosides GD2, GM3, and GD3 may potentially prevent gangliosides from inducing T-cell dysfunction.…”
Section: Molecular Mechanisms Of Immune Evasion By Tumorsmentioning
confidence: 99%
“…This novel immunoregulatory mechanism of tumor gangliosides—inhibition through enhancement of MDSC number and their function in tumors—is complemented by direct inhibitory effects of gangliosides on cytotoxic T cell function (29), suggesting a highly effective immunosuppressive process that tumors may use early on to implant and establish themselves, and a process that links rapid ganglioside metabolism to enhanced tumor growth. The deficit of infiltrating MDSC in ganglioside-poor DKO tumors may also in part explain the negative impact that the absence of gangliosides has on another process important to tumor growth, angiogenesis (30).…”
Section: Resultsmentioning
confidence: 99%
“…Tumor-associated gangliosides are also shed to microenvironment and detected in sera of cancer patients. There, they can affect functions of immune cells, e.g., inhibit CTL cytotoxicity and on the contrary attract myeloid derived suppressor cells [30,31]. Finally, in 2014, Liu et al showed that gangliosides enhance tumor angiogenesis, by comparing tumor vasculature generated in mice by wild type and GM3 synthase/GM2 synthase deficient embryonic fibroblasts that were stably transfected with c-myc and H-Ras.…”
Section: Gangliosides Are Tumor-associated Antigensmentioning
confidence: 96%